A comparison of long-term efficacy of K-rod-assisted non-fusion operation and posterior lumbar interbody fusion for single-segmental lumbar disc herniation. (January 2022) - Cheng, Xue-liang; Qu, Yang; Dong, Rong-peng; Kang, Ming-yang; Zhao, Jian-wu
Highlights: The study reports a non-fusion approach for the treatment of LDH to avoid ASD. The long-term clinical effect of k-rod non-fusion surgery for LDH was presented. This study explains the advantages of k-rod from multiple perspectives. The advantages include clinical symptoms, spinal activity, spinal balance, etc. Abstract: K-rod-assisted non-fusion surgery for the treatment of lumbar disc herniation has been proven to have short-term clinical efficacy. Meanwhile, its long-term effects have not been examined. To observed the long-term clinical efficacy of K-rod-assisted non-fusion operation, this study retrospectively analyzed 22 patients with lumbar disc (L4/5) herniation who underwent K-rod-assisted non-fusion operation (n = 13) or PLIF (n = 9). They were followed-up for more than 5 years. The operation times and blood loss were significantly reduced in the K-rod group compared to the PLIF group. At the last follow-up, the clinical outcomes of the K-rod group were improved compared to those of the PLIF group as observed by the VAS score, JOABPEQ, and ODI. Imaging outcomes at the last follow-up indicated that the loss of height in the L3/4 and L5/S1 intervertebral space, the ROM of L3/4 and L5/S1, and the incidence of adjacent segment degeneration in the PLIF group were significantly higher than those in the K-rod group. According to Pfirrmann grading, Modic changes, and UCLA grading, the incidence of adjacent segment degeneration was 55.6% in the PLIF group and 15.4% in the K-rod group. Changes in spino-pelvic parameters between the two groups were as follows: pelvic index remained unchanged, pelvic tilt angle increased, and lumbar lordosis and sacral slope decreased. Therefore, compared to PLIF, single-segment lumbar disc herniation using K-rod-assisted non-fusion surgery resulted in better long-term clinical efficacy. Our results demonstrate that this procedure can delay adjacent segment degeneration after lumbar surgery.